To simplify the expression \((4x^3)^2\), we will use the properties of exponents.
-
First, apply the power of a product rule, which states that \((ab)^n = a^n b^n\). In this case, \(a = 4\) and \(b = x^3\):
\[ (4x^3)^2 = 4^2 (x^3)^2 \]
-
Now calculate \(4^2\) and \((x^3)^2\):
\[ 4^2 = 16 \quad \text{and} \quad (x^3)^2 = x^{3 \cdot 2} = x^6 \]
-
Bringing everything together:
\[ (4x^3)^2 = 16x^6 \]
Now we have simplified \((4x^3)^2\) to \(16x^6\).
Regarding your question about whether the answer is \(8 \times 64 \times 6^6\) or \(16 \times 5\), the correct simplified expression is neither. The simplification of the original expression is \(16x^6\).